Characterizing a Populated Riparian Zone - Mah, Yau Seng (Scientific Research Publishing, 2014)
Developments adjacent to river, over the years, have impacted the ecological systems along riparian zones. This paper is to explore the changes occurring in a populated riparian zone. For over 35 years, the nipah swamps along the study site at the edge of Kuching city, Sarawak, Malaysia are subjected to human disturbances. Once a nipah forest is dominated by Nypa fruticans, the study site is being replaced by Sonneratia caseolaris—a mangrove forest. Both plants are indigenous to Southeast Asia region. We observe in the study site that Nypa fruticans, habitually a dominant species, is weakened when human disturbances are high, and leads to event taken over by Sonneratia caseolaris. We point out that Sonneratia caseolaris behaves intrusively rather than neighborly in disturbed systems. Here, we suggest that the plant also has high resistance towards human disturbances. This is a growing behavior contradictory to reports of Sonneratia caseolaris in natural systems.